2021
DOI: 10.3390/ijerph18031347
|View full text |Cite
|
Sign up to set email alerts
|

Does Work Disability Contribute to Trajectories of Work Participation before and after Vocational Labour Market Training for Job Seekers?

Abstract: The contribution of ill-health to labour market participation in relation to vocational training is unclear. Using nationally representative Finnish register data on 42,691 vocational labour market trainees in 2008–2010, we constructed latent trajectory groups of work participation in the open labour market three years before and after training, identifying groups called “High–High”, “High–Low”, “Low–High”, and “Low–Low”. We plotted further patterns of labour market participation within these trajectory groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…However, almost 30% of the LMT participants have been shown to have a work disability background. 15 A Danish study found positive employment effects of ALMPs among sick-listed workers, but the study did not have a non-sick-listed comparison group. 16 A Finnish study found that those with previous work disability were more often employed before LMT, but also experienced a stronger decline in their work participation after the training.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, almost 30% of the LMT participants have been shown to have a work disability background. 15 A Danish study found positive employment effects of ALMPs among sick-listed workers, but the study did not have a non-sick-listed comparison group. 16 A Finnish study found that those with previous work disability were more often employed before LMT, but also experienced a stronger decline in their work participation after the training.…”
Section: Introductionmentioning
confidence: 98%
“… 16 A Finnish study found that those with previous work disability were more often employed before LMT, but also experienced a stronger decline in their work participation after the training. 15 Furthermore, work participation after LMT is likely affected by the diagnosis of work disability. While no studies exist on the association between diagnostic history and work participation among ALMP participants, studies have consistently shown that especially mental disorders are generally associated with poorer labour market attachment.…”
Section: Introductionmentioning
confidence: 99%